Sociodemographic aspects and functional capacity associated with physical violence in hospitalized elderly people. - Lopes da Silva Brandão, Bárbara Maria; Nascimento de Araújo-Monteiro, Gleicy Karine; Clemente dos Santos-Rodrigues, Renata; Queiroga Souto, Rafaella; Gomes, Idalina Delfina; de Oliveira Reis, Igor (Rev Rene, 2023)
Objective: to analyze the association of sociodemographic aspects and functional capacity with physical violence in hospitalized elderly people. Methods: this was a multi-center, cross-sectional study of 323 elderly people treated at two university hospitals. The Conflict Tactics Scales, the scales for assessing basic and instrumental activities of daily living and a questionnaire adapted for assessing advanced activities of daily living were used. The data was analyzed using descriptive and inferential statistics. Results: individual activities of daily living were associated with major physical violence, indicating an inversely proportional relationship between the variables, and independent elderly people for these activities are those who do not experience major physical violence (p=0.037). Conclusion: the functional independence for instrumental activities of elderly inpatients is related to a lower probability of being a victim of physical violence. Contributions to practice: the study points to unique findings in the relationship between physical violence and functional capacity, so that each type of activity of daily living can result in a different outcome for physical violence. It also confirms the importance of individual and contextualized assessments in the hospital environment, which can influence the conditioning factors for this condition.